Optimizing the Performance of Unit IV Kamneg Satintelijen Security Police Grobogan Through Early Detection Activities to Suppress Curanmor at Grobogan Police Station - Faranzandi, Hanif (Advances in Police Science Research Journal, 2024)
One of the crimes that has a fairly high number in Grobogan District Police is the crime of motor vehicle theft. Motor vehicle theft is a crime with a state security dimension, which is the responsibility of Unit IV of the State Security Intelligence Unit of the Grobogan Resort Police. In this regard, the author considers it necessary to optimize the performance of Unit IV State Security of the security intelligence unit of the Grobogan Resort Police through early detection activities in order to suppress curanmor in the Grobogan Resort Police. In the conceptual literature, the author uses several theories and concepts as an analysis knife, namely: Competency theory, Management theory, Cooperation theory, SWOT Analysis theory, Optimization concept, Performance concept, the concept of Unit IV of the State Security Intelligence Unit, the concept of Early Detection, the concept of Motor Vehicle Theft. The research was conducted using qualitative methods and field research to obtain direct data. Primary and secondary data sources use data triangulation to obtain data validity. The findings of this research are (1) the competence of the personnel of Unit IV of the State Security Intelligence Unit of the Grobogan Resort Police is still lacking, found personnel who have not conducted S-1 general education, and some personnel have not carried out Vocational education and personnel development education, as well as lack of discipline and violations. (2) Management of the implementation of early detection was found in the implementation of early detection has not been fully adapted to Perkabik No. 1 of 2013 concerning Intelligence Investigation, from the security intelligence function does not have preliminary data of curanmor, personnel assigned not according to qualifications, and the non-use of existing equipment and equipment. (3) The cooperation is not good, it was found that there was never any information report about curanmor that went to the criminal investigation. The conclusions in this final project are (1) personnel competence is still inadequate; (2) management of early detection implementation must be improved and adjusted to Perkabik No. 1 of 2013 concerning Intelligence Investigation; (3) cooperation between the Technical Function of Security Intelligence and the Technical Function of Criminal Investigation is not good due to lack of communication, coordination and collaboration between the Technical Function of Security Intelligence and the Technical Function of Criminal Investigation.